Association of Adverse Events With Antibiotic Treatment for Urinary Tract Infection. (19th July 2021) - Butler, Anne M; Durkin, Michael J; Keller, Matthew R; Ma, Yinjiao; Powderly, William G; Olsen, Margaret A
Abstract: Background: Little is known about the relative harms of different antibiotic regimens prescribed to treat uncomplicated urinary tract infection (UTI). We sought to compare the risk of adverse events associated with commonly used oral antibiotic regimens for the outpatient treatment of uncomplicated UTI. Methods: Using data from the IBM® MarketScan® Commercial Database, we identified 1 169 033 otherwise healthy, nonpregnant women aged 18–44 years with uncomplicated UTI who initiated an oral antibiotic with activity against common uropathogens from 1 July 2006 to 30 September 2015. We used propensity score–weighted Kaplan-Meier methods and Cox proportional hazards regression models to estimate the association between antibiotic agent and adverse events. Results: Of 2 first-line agents, trimethoprim-sulfamethoxazole (vs nitrofurantoin) was associated with higher risk of several adverse drug events including hypersensitivity reaction (hazard ratio, 2.62; 95% confidence interval, 2.30–2.98), acute renal failure (2.56; 1.55–4.25), skin rash (2.42; 2.13–2.75), urticaria (1.37; 1.19–1.57), abdominal pain (1.14; 1.09–1.19), and nausea/vomiting (1.18; 1.10–1.28), but a similar risk of potential microbiome-related adverse events. Compared with nitrofurantoin, non–first-line agents were associated with higher risk of several adverse drug events and potential microbiome-related adverse events including non– Clostridium difficile diarrhea, C. difficile infection, vaginitis/vulvovaginal candidiasis, and pneumonia. Treatment duration modified the risk of potential microbiome-related adverse events. Conclusions: The risks of adverse drug events and potential microbiome-related events differ widely by antibiotic agent and duration. These findings underscore the utility of using real-world data to fill evidentiary gaps related to antibiotic safety. Abstract : In this cohort study of commercially insured women with uncomplicated urinary tract infection, risks of adverse drug events and potential microbiome-related adverse events were generally lower for nitrofurantoin than for other agents. Treatment duration modified the risk of potential microbiome-related adverse events.